Arabidopsis thaliana chromosome 4 replicates in two phases that correlate with chromatin state. - Tae-Jin Lee; Pete E Pascuzzi; Sharon B Settlage; Randall W Shultz; Milos Tanurdzic; Pablo D Rabinowicz; Margit Menges; Ping Zheng; Dorrie Main; James A H Murray; Bryon Sosinski; George C Allen; et al. (PLoS Genetics, 2010)
DNA replication programs have been studied extensively in yeast and animal systems, where they have been shown to correlate with gene expression and certain epigenetic modifications. Despite the conservation of core DNA replication proteins, little is known about replication programs in plants. We used flow cytometry and tiling microarrays to profile DNA replication of Arabidopsis thaliana chromosome 4 (chr4) during early, mid, and late S phase. Replication profiles for early and mid S phase were similar and encompassed the majority of the euchromatin. Late S phase exhibited a distinctly different profile that includes the remaining euchromatin and essentially all of the heterochromatin. Termination zones were consistent between experiments, allowing us to define 163 putative replicons on chr4 that clustered into larger domains of predominately early or late replication. Early-replicating sequences, especially the initiation zones of early replicons, displayed a pattern of epigenetic modifications specifying an open chromatin conformation. Late replicons, and the termination zones of early replicons, showed an opposite pattern. Histone H3 acetylated on lysine 56 (H3K56ac) was enriched in early replicons, as well as the initiation zones of both early and late replicons. H3K56ac was also associated with expressed genes, but this effect was local whereas replication time correlated with H3K56ac over broad regions. The similarity of the replication profiles for early and mid S phase cells indicates that replication origin activation in euchromatin is stochastic. Replicon organization in Arabidopsis is strongly influenced by epigenetic modifications to histones and DNA. The domain organization of Arabidopsis is more similar to that in Drosophila than that in mammals, which may reflect genome size and complexity. The distinct patterns of association of H3K56ac with gene expression and early replication provide evidence that H3K56ac may be associated with initiation zones and replication origins.